The GAS6-AXL signaling network is a mesenchymal (Mes) molecular subtype-specific therapeutic target for ovarian cancer - Antony,J; Tan,TZ; Kelly,Z; Low,J; Choolani,M; Recchi,C; Gabra,H; Thiery,JP; Huang,RY-J (Science Signaling, 2016)
Ovarian cancer is a complex disease with heterogeneity among the gene expression molecular subtypes (GEMS) between patients. Patients with tumors of a mesenchymal (“Mes”) subtype have a poorer prognosis than patients with tumors of an epithelial (“Epi”) subtype. We evaluated GEMS of ovarian cancer patients for molecular signaling profiles and assessed how the differences in these profiles could be leveraged to improve patient clinical outcome. Kinome enrichment analysis identified AXL as a particularly abundant kinase in Mes-subtype tumor tissue and cell lines. In Mes cells, upon activation by its ligand GAS6, AXL coclustered with and transactivated the receptor tyrosine kinases (RTKs) cMET, EGFR, and HER2, producing sustained extracellular signal–regulated kinase (ERK) activation. In Epi-A cells, AXL was less abundant and induced a transient activation of ERK without evidence of RTK transactivation. AXL-RTK crosstalk also stimulated sustained activation of the transcription factor FRA1, which correlated with the induction of the epithelial-mesenchymal transition (EMT)–associated transcription factor SLUG and stimulation of motility exclusively in Mes-subtype cells. The AXL inhibitor R428 attenuated RTK and ERK activation and reduced cell motility in Mes cells in culture and reduced tumor growth in a chick chorioallantoic membrane model. A higher concentration of R428 was needed to inhibit ERK activation and cell motility in Epi-A cells. Silencing AXL in Mes-subtype cells reversed the mesenchymal phenotype in culture and abolished tumor formation in an orthotopic xenograft mouse model. Thus, AXL-targeted therapy may improve clinical outcome for patients with Mes-subtype ovarian cancer.